Polyhydroxyalkanoates Production By Cupriavidus Necator Transformants Harboring Polyhydroxyalkanoate Synthase Of Chromobacterium Sp. Usm2 (Phaccs) And Its Potential Application For Lipase Assay Kit - Tang, Hui Jia (2024)
Polyhydroxyalkanoates (phas) are biopolyesters produced by microorganisms as carbon storage in the presence of abundant carbon sources and the limitation of growth nutrients. Poly(3-hydroxybutyrate-co-4-hydroxybutyrate) [p(3hb-co-4hb)] has been used for industrial applications, including packaging, biodegradable plastics, medical devices, and biomedical applications, owing to its biodegradability properties. Chromobacterium sp. Usm2 was isolated in langkawi, malaysia, and was able to accumulate pha. Pha synthase of chromobacterium sp. Usm2 (phaccs) was able to polymerize various monomers such as 3-hydroxybutyrate (3hb), 3-hydroxyvalerate (3hv), and 3-hydroxyhexanoate (3hhx) from carbon sources or precursors due to its broad substrate specificity. To date, there is no report on the potential of phaccs to produce p(3hb-co-4hb) copolymer. In this study, a series of optimization tests and pha biosynthesis were performed to investigate the potential of the heterologous expression of phaccs in c. Necator transformants to produce p(3hb-co-4hb) using 4hb-structurally related precursors such as 1,6-hexanediol, 1,4-butanediol, γ-butyrolactone, and sodium 4-hydroxybutyrate. The polymers obtained were then further characterized to determine their monomer compositions, thermal properties, and lipase depolymerizing activity.